Impact of the COVID-19 pandemic in patients with a previous history of premature myocardial infarction - Meral Kayikcioglu; Ozlem Kuman Tuncel; Lale Tokgozoglu (Elsevier, 2020)
Objectives: The coronavirus-disease-2019 (COVID-19) pandemic has led to the restructuring of health-services to prioritize the treatment of COVID-19. The severe restrictions on daily life affected the management of chronic diseases. Patients with a previous history of premature myocardial infarction (MI) are a vulnerable group requiring frequent and continued medical attention both in the pandemic and non-pandemic era. The present study was conducted to provide insight into the impact of COVID-19 outbreak on heart-healthy lifestyle and management of patients with a history of premature MI. Methods: This cross-sectional study included 170 consecutive patients with a history of premature MI who were already in regular follow-up in a tertiary out-patient prevention clinic before the pandemic. Inclusion criteria included age ≥18 years and being on regular follow up with the diagnosis of premature MI (documented MI before the age of 55 years) at least for one year. All patients were contacted by phone-call and replied to a 23-item questionnaire measuring the impact of the pandemic on the management, healthy lifestyle habits, and anxiety level. Results: One patient died due to COVID-19 infection; therefore the analyses were conducted in 169 patients (age: 47.67 ​± ​11.84 years, 21.3% women). The median age at first MI was 39 (IQR 10) years and the median time elapsed since the first MI was 7 years (IQR 10). The study population was highly compliant with the follow-up visits (78.1%) and pharmacological therapy (97%) before the pandemic according to the medical files. The majority (82.2%) of the patients were aware that having a history of premature MI would increase the risk and harm of COVID-19. Anxiety level increased in 62.7% of the study patients. Overall, 65.7% of the patient group reported a disruption at least in ≥1 component(s) of healthy life-behaviors (non-compliance with the heart-healthy diet, an increase in alcohol intake, an increase in smoking, and/or reduced physical activity) since the emergence of the outbreak. The anxiety level (p ​= ​0.001) and the prevalence of appetite change (p ​< ​0.0001) and weight gain (p ​< ​0.0001) was lower in the lifestyle compliant group than the non-compliant group. Avoidance of seeking medical care was reported in 33.7% of the patients. Statin use was 99.4% before the pandemic and decreased to 89.9% (p ​< ​0.0001) ​despite the fact that medications were reimbursed and widely available. Conclusions: The COVID-19 pandemic significantly affected the heart-healthy lifestyle and anxiety levels of patients with a history of premature MI who were already in regular follow-up in a tertiary prevention clinic and led to significant avoidance of medical care. More rigorous follow-up, education, and reassurance of these patients with telemedicine are necessary for the prevention of further increase in their risk.